The Dialectics of Maria Zlotina - Yuriy Myelkov (tripleC: Communication, Capitalism & Critique)
In this paper I review the system of dialectical philosophy of Maria Zlotina, one of representatives of Kiev school of Russian and Ukrainian philosophy of the 20th c. That philosophy is an original conception of materialist dialectics, where the process of cognition appears as the reflection of objective development process of the reality. Development is presented as self-motion of the object out of its inner contradiction, in which process oppositions of chance and necessity, whole and part, determination and indetermination, singular and general are being dialectically resolved. It is stressed that universality of dialectical method lies in it demanding to consider each specific moment in concrete way. The conclusion is made that dialectical method of cognition is in demand and is presumed by contemporary science of self-organization and general current of contemporary philosophical thinking, particularly, in order to understand specificity of situations of complexity and instability.